PERAN ORANGTUA PADA REGULASI EMOSI ANAK AUTIS - Festa Yumpi-R (Universitas Muhammadiyah Jember, 2016)
Problematic emotional responses, such as tantrums and anger outbursts,are surprisingly common in children with autism spectrum disorder (ASD). ASDis characterized by impaired emotion regulation that results in deficits modulatingemotional responses. Indeed, clinical reports and a few initial empirical studiesprovide evidence of severe impairments in emotional functioning among childrenwith ASD. However, significant person such as parents, teacher and clinicianshave long noted the importance of emotional problems and to find the way how tohelp them to regulate of emotion. A case study design was used to explore theauthentic experience of 3 parents with children of 3-9 years old who werediagnosed with autism syndrome. How parent‘s roles to treat their children toachieve emotion regulation were analized by using thematic analysis. The resultshowed parents provided vehicle for children to regulate emotion, such asappropriate voice to make instruction, massaged the body, food diet of CFGFSF(Casein Free, Gluten Free and Sugar Free), extinction, identified of stimuluswhich triggered of disregulation emotion and gave information of confiningbehavior. Results suggested a potential factor about the importantance the role ofparent’s ability to regognize some treatments to help emotion regulation forchildren with ASD.